Why Do Firms Hold Cash? Evidence from EMU Countries - Vilela, A. S. (European Financial Management Association 2003 Annual Conference, 2003)
This paper investigates the determinants of corporate cash holdings in EMU countries. Our results suggest that cash holdings are positively affected by the investment opportunity set and cash flows and negatively affected by asset's liquidity, leverage and size. Bank debt and cash holdings are negatively related, which supports that a close relationship with banks allows the firm to hold less cash for precautionary reasons. Firms in countries with superior investor protection and concentrated ownership hold less cash, supporting the role of managerial discretion agency costs in explaining cash levels. Capital markets development has a negative impact on cash levels, contrary to the agency view.